Politics of Identity and Democratic Consolidation in Nigeria: A Case Study of 2023 Presidential Election in Lagos State, Nigeria - Moshood, Abdul-Wasi Babatunde; Orunbon, Nurudeen Olalekan (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
This study delves into the intricate nexus between politics of identity and democratic consolidation, focusing on the context of the 2023 presidential election in Lagos State, Nigeria. The research aimed to discern the impact of identity-related factors, namely ethnicity, religion, and region, on the process of democratic consolidation. Through the use of structured questionnaires and statistical analysis, data was collected from 150 participants across ten local governments in Lagos West senatorial district. The findings underscore the significance of politics of identity in shaping the political landscape of Lagos State during the 2023 presidential election. The study reveals compelling relationships between politics of identity and democratic consolidation. Firstly, it illuminates the pivotal role played by ethnicity in influencing political behaviour and electoral outcomes. Secondly, it highlights the relevance of religious identity in shaping political attitudes and decisions. Lastly, it emphasizes the continued significance of regional identity in the political discourse and consolidation process. In light of these findings, this study offers several recommendations to stakeholders in Lagos State's political arena. These recommendations advocate for inclusive politics, civic education, interfaith and interethnic dialogues, transparent electoral practices, equal representation, data-driven policies, grassroots engagement, effective conflict resolution mechanisms, and responsible media reporting. The ultimate goal is to foster a more inclusive, harmonious, and consolidated democratic system in Lagos State.